Eurycomanone induce apoptosis in HepG2 cells via up-regulation of p53 - Zakaria, Yusmazura; Rahmat, Asmah; Lope Pihie, Azimahtol Hawariah; Abdullah, Noor Rain; Houghton, Peter J. (BioMed Central, 2009)
Background: Eurycomanone is a cytotoxic compound found in Eurycoma longifolia Jack. Previous studies had noted the cytotoxic effect against various cancer cell lines. The aim of this study is to investigate the cytotoxicity against human hepato carcinoma cell in vitro and the mode of action. The cytotoxicity of eurycomanone was evaluated using MTT assay and the mode of cell death was detected by Hoechst 33258 nuclear staining and flow cytometry with Annexin-V/propidium iodide double staining. The protein expression Bax, Bcl-2, p53 and cytochrome C were studied by flow cytometry using a spesific antibody conjugated fluorescent dye to confirm the up-regulation of p53 and Bax in cancer cells.